Role of nurses from the perspective of the hipertensivosuser hypertensive - Ana Débora Assis Moura; Mirna Garcia de Mendonça; Guldemar Gomes de Lima; Leiliane Martins Farias; Aline Rodrigues Feitosa; Emilia Soares Chaves (Universidade Federal do Ceará, 2012)
With the objective of describing the user's view of hypertension on follow-up of the nurse in a Basic Health Unit, nine patients of a Basic Care Unit of Fortaleza-CE, Brazil, were interviewed from August to September 2008. From the users' data analysis three categories were identified: patient's follow up by team nurse; view of hypertensive patient on the pathology follow-up; and the patients´ proposals to improve care. It was observed that the patients were satisfied with the assistance offered, however they considered more important the transcription of the prescription. They suggested reduction of waiting lines and increase of medical appointments. It was concluded that the users didn't identify the nursing professional in appointments, although they demonstrated satisfaction concerning the assistance and the control of blood pressure.